Ophelia : a novel - Klein, Lisa M., 1958-; Shakespeare, William, 1564-1616. (New York : Bloomsbury : Distributed to the trade by Holtzbrinck Publishers, 2006)
In a story based on Shakespeare's Hamlet, Ophelia tells of her life in the court at Elsinore, her love for Prince Hamlet, and her escape from the violence in Denmark.
HornBook Gde
Sch Libr Jnl
VOYA
LMC
12-19.
7-12.